781. COVID-19 Outcomes in the Immunocompromised Population of the COVID-19 Community Research Partnership. (15th December 2022) - Williamson, John C; Strylewicz, Gregory B; DeWitt, Michael E; Uschner, Diane; Soni, Ashvi; Mongraw-Chaffin, Morgana; Dantuluri, Keerti L; Hinkelman, Amy; Gibbs, Michael A; Lagarde, William H; Weintraub, William; Bott, Matthew; et al.
Abstract: Background: The COVID-19 Community Research Partnership (CCRP) is a large multicenter healthcare system-based study of the COVID-19 pandemic, including factors impacting risk of infection and hospitalization. The CCRP includes a subset of immunocompromised (IC) participants with varying vaccination status over time. Methods: We conducted an observational cohort study of 2, 515 IC and 41, 941 non-IC CCRP participants who contributed electronic health record data and daily electronic surveys to self-report COVID-19 symptoms, test results, and vaccinations from April 2020 to March 2022. The IC population included those with stem cell transplant, HIV, cancer, autoimmune disease, or solid organ transplant. The latter 3 must have also had an active systemic therapy to meet the IC condition (e.g. chemotherapy, immune modulator, steroid). Logistic regression was used to investigate risk of COVID-19 and hospitalization among IC participants and according to vaccine status within viral variant time periods (pre-delta, delta, omicron). Results: IC conditions included cancer (51%), autoimmune (41%), solid organ/stem cell transplant (9%), and HIV (7%). The IC group was older and had more comorbidities. 95% of vaccine recipients received an mRNA vaccine. More vaccine breakthrough infections occurred in the IC group than non-IC group (36.1% vs 29.5%, p< 0.001). IC participants were less likely to remain COVID-19 free over time if vaccinated but not boosted (Fig 1A). However, after receiving a booster there was no difference in COVID-19 cases between the groups (Fig 1B). IC participants were more likely to be hospitalized with COVID-19 (OR 2.85; 95% CI 1.69–4.76), but vaccination reduced risk for hospitalization (OR 0.26; 95% CI 0.08–0.8). Receipt of a booster dose reduced risk of COVID-19 among IC participants during the delta wave (IRR 0.52; 95% CI 0.28–0.94) but not during omicron. However, during omicron risk of hospitalization in the IC group was reduced by a booster dose (OR 0.13; 95% CI 0.02–0.72). Figure 1. Proportion Remaining Free of COVID-19 Conclusion: IC individuals were at increased risk for COVID-19 hospitalizations and breakthrough infections. After receiving a booster, IC participants were conferred the same level of protection from infection as their non-IC counterparts, highlighting the importance of boosters for these individuals. Disclosures: All Authors : No reported disclosures.